A sandwich-structured intelligent anti-icing/de-icing film with ice-oriented power self-regulating performance. Issue 34 (16th August 2022) - Liu, Xiaolin; Zhu, Yantong; Wang, Zelinlan; Ma, Zheng; Zhao, Zehui; Zhang, Deyuan; Chen, Huawei
Abstract : A smart electrothermal anti-icing/de-icing film based on the PTC effect can self-regulate heating power according to ice distribution. Abstract : Ice accretion on fast-moving complex surfaces like aircraft wings and wind turbine blades is generally uneven and varies with the various flow fields. The developed active anti-icing and de-icing techniques are generally not self-adaptive to uneven and variable ice accretion, leading to mismatching of energy output and ice distribution and thus the waste of energy. Highly efficient anti-icing/de-icing techniques with ice-oriented power self-regulating performance are urgently needed. Herein, a sandwich-structured intelligent electrothermal anti-icing/de-icing composite film with ice-oriented heating power output ability is proposed for the first time. Based on a positive temperature coefficient (PTC) effect and a simple sandwich structure, this smart film can spontaneously detect the cold load distribution on it and automatically maintain high heating power at ice contact regions, while lower the power output at non-contact regions. This smart film can even depict the real-time ice location and area aided by patterned electrodes. The results can help to provide insights into the design of safe, intelligent and highly efficient anti-icing/de-icing films and facilitate their large-scale application.